Feasibility of Online High-Intensity Interval Training (HIIT) on Psychological Symptoms in Students in Lockdown During the COVID-19 Pandemic: A Randomized Controlled Trial - Philippot, Arnaud; Moulin, Pauline; Charon, Marie-Hélène; Balestra, Costantino; Dubois, Vincent; de Timary, Philippe; De Volder, Anne; Bleyenheuft, Yannick; Lambrechts, Kate (Frontiers in Psychiatry, 2022)
Objective We aimed to evaluate the feasibility of an online High-Intensity Interval Training (HIIT) program on clinical psychological symptoms in higher education students in the context of the COVID-19 pandemic lockdown. Materials and Methods During the lockdown, 30 students aged 18–25 years, who had been screened previously with a cut-off score ≥5 in the Generalized Anxiety Disorder-7 (GAD-7) questionnaire, were randomly assigned to either the 4-week HIIT program with three sessions per week conducted through online videos, or a no-intervention control group. The primary outcome was the feasibility assessment. The secondary outcome was a psychological self-report with the 21-items Depression, Anxiety, and Stress Scale (DASS-21). Assessment and intervention were performed in compliance with social distancing rules. Results Two participants in the HIIT were lost to follow-up, leaving 13 participants vs. 15 in the control group. We observed high adherence (87%) and complete safety for mental and physical status with the HIIT intervention delivered by online videos. The Mann-Whitney test demonstrated a significant (group × time, P-Value = 0.046) reduction of clinical stress symptoms and a trend (group × time, P-Value = 0.08) toward reduction of clinical depression symptoms, both favoring the HIIT group. No significant (group × time, P-Value = 0.118) interaction was found for anxiety symptoms. Conclusion The online HIIT program was found to be feasible and safe in a clinical sample of young adults, who were experiencing social and physical restrictions due to COVID-19. HIIT reduced stress and depressive symptoms and thus these preliminary results show promise for broader application among higher education students during the present lockdown necessitated by the global COVID-19 health crisis.